Pemanfaatan Bambu Tabadiku sebagai Agregat Kasar Pada Pengujian Kuat Tekan Beton - Hartati Kapita; Elfira Resti Mulya (Jurnal Serambi Engineering, 2021)
The use of bamboo as building materials has occurred for a long period, especially in a simple construction system. Bamboo can be utilized as a building material due to its advantages. One of the advantages is that bamboo has a significantly low density so  it can reduce the density of concrete whose main material is gravel. Gravel is a natural building material is formed from unconsolidated rock fragments, such as rock pieces or small rocks. Gravel is commonly found in Indonesia because there is a lot of availability. This research aims to utilize local bamboo resources as building materials. Bamboo is used as an alternative substitute for gravel aggregate in the concrete mixing. The research method was experimental laboratory work. The results showed that the use of bamboo as an aggregate can only be used in non-structures, this is because the rate  of absorption of bamboo against water is quite high. While the compressive strength of the concrete produced by  mixing 100 % bamboo aggregate has an average value of 3.09 MPa and mixing 50 % of bamboo has an average value of 6.01 MPa. Therefore, the quality of the concrete cannot be used for building structures, but  only be used in non-structural buildings.